THE IMPACT OF SLOW AND CIRCULAR FASHION ON CONSUMERS’ CHOICE OF CLOTHING APPAREL - Daah Siaw, Stella; Opoku, Moses; Baiden, Sarah (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
In the current period characterised by heightened awareness of environmental sustainability and ethical consumerism, the fashion industry is undergoing a significant transformation as it embraces slow and circular fashion practices. This development has been very promising due to the environmental dangers associated with fast fashion. There are many factors that shape consumer preferences within the context of sustainable fashion. The emergence of slow fashion, which is defined by deliberate consumption and ethical manufacturing and circular fashion, prioritises closed-loop systems and responsible end-of-life practices, have presented an attractive and a new dimension of producing environmental-friendly fashion for consumers. Irrespective, of the global efforts in protecting the environment through the right choice of clothes, which is supported by the slow fashion paradigm, some people are still glued to fast fashion model without necessarily considering its associated impacts. This study examines the impact of slow and circular fashion on customers' clothing choices and their effects on the environment. Again, it underscores the psychological, social, economic, and environmental issues that influence the adoption of slow and circular fashion. Data were obtained via online questionnaire. The study revealed that the development of slow and circular fashion models among customers has been impeded due to a deficiency in proactive communication from various retailers who contribute to the sustainability mission.